La belle sauvage - Pullman, Philip, 1946- (New York : Alfred A. Knopf, 2017)
When Malcolm finds a secret message inquiring about a dangerous substance called Dust, he finds himself embroiled in a tale of intrigue featuring enforcement agents from the Magisterium, a woman with an evil monkey daemon, and a baby named Lyra.
Keywords: Belacqua, Lyra (Fictitious character) -- Juvenile fiction; Belacqua, Lyra (Fictitious character) -- Fiction; Young adult fiction; Fantasy fiction